2015
DOI: 10.4025/cienccuidsaude.v14i2.17696
|View full text |Cite
|
Sign up to set email alerts
|

<b>Sofrimento moral dos agentes comunitários de saúde/ Moral distress of health community agents

Abstract: Este texto se origina da dissertação de mestrado intitulada: "Estratégia de saúde da família e vivência de sofrimento moral dos agentes comunitários de saúde", sustentada no Programa de Pós-Graduação em Enfermagem da Universidade Federal do Rio Grande-FURG.. Pesquisa financiada pelo CNPq i *Enfermeira. Mestre em Enfermagem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…A falta de comunicação e companheirismo entre equipes de trabalho, a desconsideração dos médicos, a falta de oportunidade de diálogo com gestores, a impotência para contestar decisões de outros profissionais e a pouca autonomia no trabalho são fatores que podem desencadear sofrimento moral nos profissionais da saúde (20)(21)(22) . Estes fatores foram relatados pelos profissionais da técnica radiológica no presente estudo como desencadeadores de sofrimento moral.…”
Section: Discussionunclassified
“…A falta de comunicação e companheirismo entre equipes de trabalho, a desconsideração dos médicos, a falta de oportunidade de diálogo com gestores, a impotência para contestar decisões de outros profissionais e a pouca autonomia no trabalho são fatores que podem desencadear sofrimento moral nos profissionais da saúde (20)(21)(22) . Estes fatores foram relatados pelos profissionais da técnica radiológica no presente estudo como desencadeadores de sofrimento moral.…”
Section: Discussionunclassified
“…22 Com isso, a saúde dos trabalhadores da APS é afetada, pois exige-se a reorganização do processo de trabalho, resultando em maior sobrecarga 23 , por meio de uma lógica gerencialista, que prioriza critérios empresariais de eficiência e modernização 24 . A falta crônica de pessoal nas equipes, o medo e a insegurança em relação ao desemprego, a perda de direitos trabalhistas e atrasos salariais 25 somados ao sentimento de desvalorização, frustração e impotência frente aos problemas da comunidade, aspectos que se aproximam aos encontrados neste estudo, são agravantes 26 . É comum o sofrimento psíquico provocado pela impotência e frustração diante de um processo de regulação de desempenho que enfatiza a cobrança de metas de produtividade, ritmos de trabalho excessivos e prazos curtos na produção em saúde.…”
Section: Escuta Não Efetivaunclassified
“…This fact warns us on the fragile moral sensitivity of professional performance and on the non-reflection of the subjects about its practice. In this sense, the literature emphasizes the importance of strengthening the knowledge on the moral dimension found in the different actions and omissions, 14 as well as the improvement of the competences that aim to improve the moral sensitivity of professionals before the ethical problems present in their work. 40 The deprivation of the exercise of their autonomy, understood as an institutional violence, rooted in the cycle of female oppression, 20 is justified by the professionals through arguments that disqualify the woman and place them in a position of ignorance and incapable of deciding about her body and her parturition in a discourse marked by prejudice.…”
Section: /16mentioning
confidence: 99%
“…8 The experience of being inserted in a care context marked by practices that go against the MS advocated in relation to obstetric care can lead them to moral suffering, characterized by painful psychological imbalance resulting from the impediment brought about by the environment so that the same their conduct in accordance with the ethical conduct they deem appropriate. 9 There are studies In the literature that address the moral suffering of nurses in different contexts, [10][11][12][13][14] as well as issues related to the childbirth humanization, 2,6,8,[15][16][17][18][19][20][21][22][23][24] but there are no national and international surveys that articulate the two aspects. Based on the foregoing, it is justified to carry out this study, which aimed to know the situations found in the work of nurses working in maternity and obstetric centers that can lead to moral suffering.…”
Section: Introductionmentioning
confidence: 99%